מדריכי סופרים וכוונות קבליות: מסורות מלומדות של כתיבת קמעות באשכנז הפרה-מודרנית - פלוך אגטה (מחשבת ישראל, 2025)
This article examines the evolution of Jewish scribal practices in medieval and early modern Central-Eastern Europe, focusing on the intersection between traditional scribal laws for ritual texts (STaM), kabbalistic intentional practices, and amulet-writing traditions. It argues that the concept of intentional practice performed “for its own sake” developed in the thirteenth- and fourteenth-century Ashkenaz became foundational for later kabbalistic interpretations of intentional scribal work. This study traces how the requirement of intentional writing influenced both elite kabbalistic approaches to textuality and practical scribal work in producing ritual and apotropaic objects. Through analysis of medieval Ashkenazi sources and a case study of a kabbalistic “Amulet of Four Lines,” the article demonstrates how Ashkenazi scribal traditions provided fertile ground for the integration of kabbalistic writing practices in Central-Eastern Europe prior to and independent of Lurianic kabbalistic influences. This study contributes to our understanding of how material textual objects became construed as imbued with divine potency through intentional scribal work, demonstrating continuities between regulated ritual writing and magical protective practices in the premodern Ashkenazi cultural sphere.